Flexible transparent sensors from reduced graphene oxide micro-stripes fabricated by convective self-assembly. (March 2017) - Zaharie-Butucel, Diana; Digianantonio, Lucas; Leordean, Cosmin; Ressier, Laurence; Astilean, Simion; Farcau, Cosmin
Abstract: Reduced graphene oxide (rGO) currently represents an attractive alternative material for graphene and its already well-known electronics applications. Due to its liquid phase processing it can be produced inexpensively on large scale, but its deposition into films/patterns of defined geometry on solid substrates remains challenging. In this work, rGO micro-stripes with controlled morphology are prepared on polyethylene terephthalate substrates by Stop&Go Convective Self-Assembly. This method allows the deposition of regular arrays of rGO stripes by independently adjusting the stripe geometry and array period in an inexpensive, clean and fast way, and without any lithographic patterning. The as-obtained rGO stripes are highly transparent, flexible and good electrical conductors, properties which are of great value for future electronic devices. We exploit these properties for fabricating for the first time a bi-functional strain and humidity sensor which is optically transparent. Graphical abstract: